2020
DOI: 10.1002/ctm2.22
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte microRNAs show biomarker potential and implicate multiple sclerosis susceptibility genes

Abstract: Background Multiple sclerosis is a demyelinating autoimmune disease, for which there is no blood‐borne biomarker. Erythrocytes may provide a source of such biomarkers as they contain microRNAs. MicroRNAs regulate protein translation through complementary binding to messenger RNA. As erythrocytes are transcriptionally inactive, their microRNA profiles may be less susceptible to variation. The aim of this study was to assess the biomarker potential of erythrocyte microRNAs for multiple sclerosis and assess the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
0
7
0
1
Order By: Relevance
“…They, lacking a nucleus, show a stable content of miRNAs. The availability of such peripheral source of EVs makes them a very interesting specimen in the study of EV-derived miRNAs in MS. A very recent study investigated, for the first time, the involvement of erythrocyte-derived EV miRNAs in MS [ 64 ]. Erythrocyte-derived EVs were purified ex vivo from isolated erythrocytes.…”
Section: Evs’ Cargo: Reservoir Of Potential Biomarkers For Msmentioning
confidence: 99%
See 2 more Smart Citations
“…They, lacking a nucleus, show a stable content of miRNAs. The availability of such peripheral source of EVs makes them a very interesting specimen in the study of EV-derived miRNAs in MS. A very recent study investigated, for the first time, the involvement of erythrocyte-derived EV miRNAs in MS [ 64 ]. Erythrocyte-derived EVs were purified ex vivo from isolated erythrocytes.…”
Section: Evs’ Cargo: Reservoir Of Potential Biomarkers For Msmentioning
confidence: 99%
“…This study highlighted that erythrocyte-derived EVs were selectively packaged and contained a majority of highly expressed miRNAs in red cells. In particular, hsa-miR-451a which is transferred from erythrocytes to endothelial cells by EVs, contributed to the loss of the integrity barrier in cerebral malaria, but it was also increased in MS patients’ plasma [ 64 ]. Actually, erythrocytes may have a role in MS due to their impaired antioxidant capacity and hemorheological changes that may contribute to BBB damage [ 64 ].…”
Section: Evs’ Cargo: Reservoir Of Potential Biomarkers For Msmentioning
confidence: 99%
See 1 more Smart Citation
“…Although each cell contains almost the same gene sequence, the gene expression varies according to different tissues, developmental stages and environmental stimuli. DNA methylation, histone modification and noncoding RNAs are three main manifestations of the epigenome 67,68 . For example, several studies revealed that DNA methylation is involved in several steps of lung cancer pathogenesis, such as cell differentiation and epithelial‐mesenchymal transition.…”
Section: Systems Biology Studies To Discover Novel Biomarkers For the Respiratory Systemmentioning
confidence: 99%
“…Предложенный подход -использовать параметры эритроцитов для прогнозирования течения заболевания -не нов. Исследование показателей красной крови как биомаркеров и предикторов активно проводится при целом ряде патологий: в кардиологической практике показатель распределения эритроцитов по объему (RDW) рассматривается как долговременный прогностический фактор течения острого инфаркта миокарда [33], величина омега-3 индекса мембран эритроцитов дает стратификацию риска развития внезапной коронарной смерти [34], острого инфаркта миокарда [35,36]; в неврологии микро-РНК эри-троцитов рассматриваются как потенциальный биомаркер течения рассеянного склероза [37]; проведен анализ уровня RDW для прогноза течения колоректального рака [38]. Настоящая работа, находясь в тренде подобных исследований, демонстрирует возможности электрических и вязкоупругих параметров эритроцитов, измеренных методом диэлектрофореза, отличающегося минимальной пробоподготовкой, высокой скоростью выполнения, малой затратностью и трудоемкостью, высокой информативностью и наглядностью [9].…”
Section: рис 6 тепловая карта (Heatmap) корреляций электрических и вя...unclassified